Sensitivity of electrophysiological activity from medial frontal cortex to utilitarian and performance feedback. - Nieuwenhuis, S; Yeung, N; Holroyd, C; Schurger, A; Cohen, J (2004)
A recent study has reported the observation in humans of an event-related brain potential component that is sensitive to the value of outcomes in a gambling task. This component, labeled medial frontal negativity (MFN), was most pronounced following monetary losses as opposed to monetary gains. In this study, we investigate the relationship between the MFN and the error-related negativity (ERN), a component elicited by feedback indicating incorrect choice performance. We argue that the two components can be understood in terms of a recently proposed theory that predicts the occurrence of such scalp negativities following stimuli that indicate that ongoing events are worse than expected. The results from two experiments using a gambling task demonstrate that the sensitivity of the MFN/ERN to the utilitarian and performance aspect of the feedback depends on which aspect is most salient. The results are consistent with the view that the two components are manifestations of the same underlying cognitive and neural process.